The Provision of Food to the Aramaean Captives in II Reg 6,22–23 - Goldstein, Ronnie (Zeitschrift für die alttestamentliche Wissenschaft, 2014)
The article investigates the meaning of the phrase ויכרה להם כרה גדולה in II Reg 6,23. An alternative sense is suggested for the Hebrew root כר“ה in this passage, Akkadian, Aramaic, and rabbinic Hebrew attesting the noun as signifying a »pile«, and accordingly the denominative verb meaning »heaping up«. It adduces Neo-Assyrian passages in which the »heaped stocks« also serve as a way of paying homage in military contexts, and two further Neo-Assyrian texts resembling the biblical account in both content and context shedding further light on the political connotation of feeding captives – namely, as a symbol of their subordination. Résumé: Cette étude est consacrée à la signification de l’expression ויכרה להם כרה גדולה en II Rois 6,23. Un sens alternatif est proposé pour la racine כר“ה dans ce passage, correspondant à l’akkadien, l’araméen et l’hébreu rabbinique, au sens de »tas«, ainsi que le verbe dénominatif »entasser« correspondant. Dans les textes néo-assyriens, l’expression »ustensiles entassés« désigne une forme de rémunération en contexte militaire; deux autres textes assyriens, qui rappellent le texte biblique par le contenu et le contexte, illustrent cet aspect politique du traitement des prisonniers, en symbole de soumission. Zusammenfassung: Dieser Artikel untersucht die Bedeutung der Wendung ויכרה להם כרה גדולה in II Reg 6,23. Für die hebräische Wurzel כר“ה wird in diesem Abschnitt eine alternative Bedeutung vorgeschlagen entsprechend dem Akkadischen, Aramäischen und rabbinischem Hebräisch, wo das Nomen als »Haufen« und das denominative Verb als »anhäufen« belegt sind. In neuassyrischen Texten dienen die »angehäuften Vorräte« als eine Art Entlohnung im militärischen Bereich; zwei weitere assyrische Texte, die in Inhalt und Kontext dem biblischen Text ähneln, beleuchten den politischen Aspekt der Gefangenenversorgung, insbesondere als ein Symbol der Unterordnung.